Assessment of Polytechnic Academic Staff Inputs into Nigeria’s National Development - Ogunkoya, Samuel A.; Enyi, Francis O.; Aremu, Sulyman S. (NIU Journal of Humanities, 2020)
The pace of Nigeria national development has been reported to be at variance with vision 20:2020 projections. This paper assessed the contributions of academics in the polytechnic system to the Nation’s development. Through the involvement of 6 polytechnics in southwest Nigeria that were purposively selected, 182 academics participated in the survey with the filling of questionnaire which sought for their opinions on the input of research and teaching effectiveness into the nation’s development. Responses were analysed with both descriptive and inferential statistics. Findings revealed that research output and teaching effectiveness contribute to national development. It was concluded that Nigeria cannot attain that development pedestal with the present teaching methods and research output quality. The study therefore recommended that one of the ways through which Nigeria can fast track her national development process is for her academics, especially those in the polytechnics who prepares students for future resource management, to possess the right knowledge, skills, experience and qualifications to drive the process by way of ground breaking research output and effective teaching delivery. Keywords: Academic Staff, National Development, Research, Nigeria, Polytechnic, Teaching.